Guardián Comunitario: Innovación en seguridad y respuesta rápida a emergencias (Innovation & Development in Engineering and Applied Science, 2024)
This work focuses on the development of a mobile panic button application to meet the security and rapid emergency response needs of the Ainche community in Chimborazo province. Field research was conducted to analyze the importance of the application and user satisfaction; additionally, a bibliographic review was carried out on agile software development methodologies. Guardian Comunitario is a mobile application developed using the SCRUM methodology, which contributes to the community's security and emergency response. To evaluate its impact, a satisfaction survey was conducted, showing that 60% of respondents consider the application easy to use; 80% perceive an improvement in communication between community members and emergency services; furthermore, the response time to emergencies was reduced from 20 to 10 minutes
Keywords: Mobile Applicationy; Quality; Development Methodology; SCRUM; Security